Motor-independent Visual Perception Skill Indexes are Related with Reading Skills in Children with Cerebral Palsy - Vahid Reza Khodabandeh; Mozhgan Farahbod; Ebrahim Pishyareh; Mehdi Rahgozar (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: Cerebral palsy is one of the most common causes of physical disability in childhood that lead to various difficulties for children. These children may have abnormalities in visual perception. Visual perception plays an important role in learning of basic childhood’s skills. This research was designed to study the relation between each of subtests of visual perception with accuracy and speed components of reading skills in school-aged cerebral palsy children. Materials & Methods: In this cross-sectional study, 24 spastic cerebral palsy students in second grade (10 girls and 14 boy) were selected be available as from Tehran’s rehabilitation clinics. Visual perception and Reading skills were evaluated with the Test of Visual Perceptual Skill-revised (TVPS-R) and Diagnostic Reading Test. Results: The results showed that between standard score of visual perception with accuracy and speed components of reading skills of cerebral palsy student were significantly correlated. Visual Discrimination with accuracy (P<0.001) and with speed (P<0.001), Visual Memory with accuracy  (P=0.002) and with speed (P=0.004), Visual-Spatial with accuracy (P<0.001) and with speed (P<0.001), Form Constancy with accuracy (P=0.003) and with speed (p<0.001), Visual Sequential Memory with accuracy (P=0.023) and with speed (P<0.028), Figure Ground Discrimination with accuracy (P=0.010) and with speed (P<0.011), Visual Closure with accuracy (p=0.009) and with speed (P<0.009) Conclusion: In general we can say that the relationship between visual perception skills with reading skills in first and second grade students with cerebral palsy is evident.